2010
DOI: 10.1021/ac902809q
|View full text |Cite
|
Sign up to set email alerts
|

Mass Spectrometric Fragmentation Analysis of Oligosialic and Polysialic Acids

Abstract: Oligosialic and polysialic acids (oligo/polySia) are characterized by high structural diversity, because of different types of sialic acids and glycosidic linkages. Although several methods have been described for the analysis of oligo/polySia, only high-performance liquid chromatography (HPLC) analysis in conjunction with 1,2-diamino-4,5-methylenedioxybenzene labeling, fluorometric C7/C9 detection, Western blotting, and matrix-assisted laser desorption/ionization time-of-flight mass spectroscopy (MALDI-TOF-MS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 30 publications
0
25
0
Order By: Relevance
“…Kakehi et al employed LC-ESI MS after derivatization with DMB examined specific distribution of SAs in animal tissues [48]. Geyer et al used MALDI-TOF MS combined with DMB derivatization and HPLC separation method analyzed mass spectrometric fragmentation of oligosialic and polysialic acids [49]. The same group later reported a method of quantification of nucleotide-activated SAs by LC-ESI MS combined DMB derivatization and HPLC separation [50].…”
Section: Derivatization Of Sialylglycans For Their Mass Spectromementioning
confidence: 99%
See 2 more Smart Citations
“…Kakehi et al employed LC-ESI MS after derivatization with DMB examined specific distribution of SAs in animal tissues [48]. Geyer et al used MALDI-TOF MS combined with DMB derivatization and HPLC separation method analyzed mass spectrometric fragmentation of oligosialic and polysialic acids [49]. The same group later reported a method of quantification of nucleotide-activated SAs by LC-ESI MS combined DMB derivatization and HPLC separation [50].…”
Section: Derivatization Of Sialylglycans For Their Mass Spectromementioning
confidence: 99%
“…So far, several methods have been reported for the characterization of oligosialic and polysialic acids, among which, derivatizationwith 1,2-diamino-4,5-methylenedioxybenzene (DMB) followed by HPLC and fluorometric detection. MALDI-TOF MS has been employed as an ultrasensitive method for the characterization of oligosialic and polysialic acids [49]. In addition, lactone formation was reported by Galuska et al [51] to stabilize polysialic acids for their analysis by MALDI-TOF MS. Lactonization was achieved with TFA and o-phosphoric acid and, of several matrices tested, 6-aza-2-thiothymine (ATT) proved to be the most satisfactory with DHB being nearly as good.…”
Section: Derivatization Of Sialylglycans For Their Mass Spectromementioning
confidence: 99%
See 1 more Smart Citation
“…The three dimensional structure of polysialic acids is influenced by many factors including inter-residue interactions and lactonization. It has been reported that the negative charge of the carboxylic acid at C-1 position of Neu5Ac is crucial in determining the conformation of polysialic acids and polysialic acids can form helical structure when the chain consists of more than ten monomers whereas at shorter lengths it occurs as linear chain [26,[48][49][50][51][52]. A three dimensional structural study of a(2-8) linked polysialic [53].…”
Section: Discussionmentioning
confidence: 99%
“…611 For a series of papers, specifically focused on mass spectrometry of intact sialoglycans, including information about the stabilization of sialic acid, see refs. [612][613][614][615][616][617][618]. For the differentiation between (α2 !…”
Section: General Remarks About the Structural Analysis Of Glycansmentioning
confidence: 99%